2018
DOI: 10.1371/journal.pone.0198702
|View full text |Cite
|
Sign up to set email alerts
|

A biphasic locomotor response to acute unsignaled high temperature exposure in Drosophila

Abstract: Unsignaled stress can have profound effects on animal behavior. While most investigation of stress-effects on behavior follows chronic exposures, less is understood about acute exposures and potential after-effects. We examined walking activity in Drosophila following acute exposure to high temperature or electric shock. Compared to initial walking activity, flies first increase walking with exposure to high temperatures then have a strong reduction in activity. These effects are related to the intensity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…In agreement with previous studies, this work shows that exposition of flies only to heat shock reduces the locomotor activity, but fasting and electric shock increases the motor behavior (Bell et al, 1985;Mohammad et al, 2016a;Ostrowski et al, 2018). However, this study contradicts previous reports which showed that isolation reduced the exploratory behavior of adult flies (Araujo et al, 2018;Neckameyer and Nieto-Romero, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with previous studies, this work shows that exposition of flies only to heat shock reduces the locomotor activity, but fasting and electric shock increases the motor behavior (Bell et al, 1985;Mohammad et al, 2016a;Ostrowski et al, 2018). However, this study contradicts previous reports which showed that isolation reduced the exploratory behavior of adult flies (Araujo et al, 2018;Neckameyer and Nieto-Romero, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…There was a general increase in locomotor activity of all flies with increase in temperature and decrease in activity following the sudden decrease in temperature to 24°C. These phenomena have been observed previously and are well documented [152]. Additionally, the median number of approaches and hot side dwells of R58E02-GAL4>UAS-Gr28bD flies that were trained at 38 or 40°C were significantly lower than those trained at 36°C (Mann-Whitney U test, p<0.019).…”
Section: Activity Testsupporting
confidence: 84%
“…There is also evidence that thermal stress has a significant negative impact on organismal energy reserves in D . melanogaster 53 , and that exposure to acute high temperatures increases both locomotor activity and metabolic rate, whereas starvation and cold exposure lead to reductions in both 5456 . Combined with the notable observation from the current study that mtDNA CN is reduced with age in males but not in females this suggests that differences in metabolic demand and efficiency in male and female flies is key to understand sexual dimorphism in lifespan and trait specific and sex dependent responses to aging.…”
Section: Discussionmentioning
confidence: 99%